A CATHODE MATERIAL - LUO HONGZE; SETENI BONANI; MATHE MKHULU; RAPULENYANE NOMASONTO (2020)
A process for producing a lithium-manganese-rich layered oxide cathode material or a lithium-manganese-rich layered oxide cathode material precursor includes co-precipitating a dissolved Li compound and a dissolved Mn salt selected from the group consisting of Mn(CH3COO)2, Mn(NO3)2, MnSO4, and mixtures thereof, from an aqueous solution, in the presence of a precipitator which reacts at least withthe dissolved Mn salt to form a carbonate, thereby providing a precipitate which includes MnCO3 and a lithium compound as a lithium-manganese-rich layered oxide cathode material precursor. The invention extends to a lithium-manganese-rich layered oxide cathode material or a lithium-manganese-rich layered oxide cathode material precursor, to an electrochemical cell, and to methods of making and operating an electrochemical cell. 一种用于生产富锂锰的层状氧化物阴极材料或富锂锰的层状氧化物阴极材料前躯体的工艺，包括：在沉淀剂的存在下，在水溶液中，共沉淀溶解的Li化合物和溶解的Mn盐，该溶解的Mn盐选自包括Mn(CHCOO)、Mn(NO)、MnSO及其混合物的组，该沉淀剂至少与该溶解的Mn盐反应以形成碳酸盐，从而提供作为富锂锰的层状氧化物阴极材料前躯体的包括MnCO和锂化合物的沉淀物。本发明扩展至一种富锂锰的层状